PENGARUH PENERAPAN METODE INQUIRI TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Aklimawati . (Jurnal Peluang, 2015)
One of the method than can is used in math toward geometry of space material is inquiri method. Inquiri method gives wide experience to students through the process of finding self with cartain steps a get a solution, therefore students can analyze and develop perceptibility. Based on this case, a problem arise that does inquiri mathod can increase students thinking ability toward geometri of space material to the students of SMAN 12 Banda Aceh. This study aims to find out the impact by using inquiri method toward the students achievement geometri of space material for grade X SMAN 12 Banda Aceh. The population of research is all of the students of grade X of SMAN 12 Banda Aceh which has students in total 150 persons consist of of 5 paralel class. The sample is chosen randomly one sample is class X2 which 32 students as control class and the other sample is class X4 which 32 students as experiment class. To get the data is this study, the researcher use test as the instrument. The collected data is processed by using statistic formula t-test and n-gain. Based on the results of analysis showd that the students who were taught by using inquiri method are better than the students who were taught without this method toward geometry of space material in grade X of SMAN 12 Banda Aceh.KeyWords: Inquiri method, thinking ability, geometry of space